2017
DOI: 10.11138/ccmbm/2017.14.3.359
|View full text |Cite
|
Sign up to set email alerts
|

Glomus tumor as a cause of oncogenic osteomalacia

Abstract: SummaryMany tumors that occasionally are benign in origin causes hypophosphatemic osteomalacia. Here we present a case of glomus tumor in a 59-year-old man with oncogenic osteomalacia. Diagnosis was made after observation of abnormal increase activity in octreotide scan. The magnetic resonance imaging showed a round lesion in left ankle joint. Surgical excision of tumor was curative and all symptoms and intractable hypophosphatemia improved after few weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…An MRI scan revealed an in-homogenous lesion in the distal area of the left leg, posterior to the tibia. According to histopathological findings, the tumor was diagnosed as a GT [ 34 ]. Frumuseanu et al reported a tumor in the medial aspect of the right knee, on a 10-year-old boy’s leg after a fall.…”
Section: Discussionmentioning
confidence: 99%
“…An MRI scan revealed an in-homogenous lesion in the distal area of the left leg, posterior to the tibia. According to histopathological findings, the tumor was diagnosed as a GT [ 34 ]. Frumuseanu et al reported a tumor in the medial aspect of the right knee, on a 10-year-old boy’s leg after a fall.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is the most obvious symptom of the disease, usually presenting as spontaneous tingling, extreme pain with the slightest touch, and intolerance to temperature changes[ 5 , 11 ]. In addition to these obvious symptoms, uncommon presentations such as tumor-induced osteomalacia were also reported, but more evidences are needed to support this discovery[ 12 ]. The disease diagnosis depends on clinical tests such as the Love test (point tenderness) and Hildreth's sign (decreased pain on exsanguination of the limb and application of a tourniquet)[ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A further MRI revealed an in-homogenous lesion in the distal area of the left leg, posterior to the tibia. The histopathological findings after complete surgical resection led to the definite diagnosis of GT (16). Another reported case was that of a GT in the medial aspect of the right knee, which appeared on the leg of a 10-year-old boy after a fall.…”
Section: Discussionmentioning
confidence: 99%